Serologic microbial associated markers can predict Crohn's disease behaviour years before disease diagnosis. Issue 12 (27th April 2016) - Choung, R. S.; Princen, F.; Stockfisch, T. P.; Torres, J.; Maue, A. C.; Porter, C. K.; Leon, F.; De Vroey, B.; Singh, S.; Riddle, M. S.; Murray, J. A.; Colombel, J. F.; et al.
Summary: Background: Patients with Crohn's disease (CD) have serologic responses to various microbial antigens. Serologic markers are associated with aggressive forms of disease and can be detected before onset of symptoms. Their utility in pre‐clinical disease or prediction of complicated disease course before diagnosis is unclear. Aim: To evaluate the pattern of serologic anti‐microbial antibodies long prior to diagnosis and the subsequent risk of complicated Crohn's disease at diagnosis. Methods: Sera from 100 US military personnel with Crohn's disease were obtained from the Department of Defense Serum Repository. For each patient, four samples were obtained at different time points before and around diagnosis, and were tested for 6 microbiota‐directed antibodies (ASCA‐IgA, ASCA‐IgG, anti‐OmpC, anti‐CBir1, anti‐A4‐Fla2 and anti‐FlaX). Associations between the presence and accumulation of Crohn's disease anti‐microbial antibodies before diagnosis and with the later development of complications were evaluated. Results: Overall, 65 patients were positive for at least one Crohn's disease associated anti‐microbial antibody in the earliest available sample, at a median of 6 years before Crohn's disease diagnosis (interquartile range, 5.6–8.2). The number of positive anti‐microbial antibodies increased up to the time of Crohn's disease diagnosis. Complicated disease developed around the time of diagnosis in 24 patients. The proportion of positive antimicrobial antibodies before diagnosis was higher in patients with complicated vs. noncomplicated Crohn's disease. There was an inverse relationship between the time to first complication and the magnitude of serologic response before diagnosis. Conclusion: The presence and accumulation of circulating anti‐microbial antibodies years before Crohn's disease diagnosis was associated with complicated Crohn's disease at or shortly after diagnosis.